Non‐response to daclatasvir and asunaprevir therapy in patients co‐infected with hepatitis C virus genotypes 1 and 2. Issue 4 (26th August 2016) - Sohda, Tetsuro; Yamauchi, Eri; Anan, Akira; Yokoyama, Keiji; Fukunaga, Atsushi; Yamauchi, Ryo; Fukuda, Sho; Takata, Kazuhide; Tanaka, Takashi; Hanano, Takayuki; Kitamura, Yuji; Morihara, Daisuke; et al.
Abstract : Direct‐acting antiviral agents for hepatitis C virus (HCV) have been developed such as combined daclatasvir (DCV) and asunaprevir (ASV) treatment. This typically enables HCV serotype 1 patients to achieve a high sustained virological response rate, but a small number of such patients fail to respond to therapy. We investigated three HCV patients who showed no response to DCV and ASV therapy. Hepatitis C genotyping was undertaken in the three patients using nested polymerase chain reaction and polymerase chain reaction direct sequencing in the core region of the HCV genome. All three patients possessed HCV serotype 1, and no mutations were identified in either the non‐structural protein 3 or 5A region. The three patients were shown to be co‐infected with HCV genotypes 1 and 2 because genotypes 2a and 2b were also identified. This is the first report into failed response to DCV and ASV therapy in patients co‐infected with HCV genotypes 1 and 2.